1994
DOI: 10.1089/jir.1994.14.205
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significance of Therapy-Induced Neutralizing Antibodies Against Interferon-β

Abstract: In A 6-month open adjuvant trial, we treated 21 patients with melanoma with natural interferon-ß (IFN-ß) (Fiblaferon, Rentschier, Laupheim, Germany), and a further 7 patients with recombinant (r)IFN-ß (Betaferon, Rentschier, Laupheim, Germany). With both IFN-ß preparations, the course consisted of three subcutaneous injections of 3 million IU per week given each week for a total of 24 weeks. All patients had stage II malignant melanoma (UICC 1979), and had had all detectable metastases removed surgically befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As previously discussed, data from clinical trials suggest that the development of NAbs may reduce the therapeutic efficacy of IFNβ therapy [4,6,8]. However, there is no consensus on the immunomodulatory role of anti-IFNβ antibodies, and some authors have published findings that refute their reported antitherapeutic effect [19][20][21]. The discrepancies among the published data may be explained by differences in both methodology and numbers of patients analysed.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, data from clinical trials suggest that the development of NAbs may reduce the therapeutic efficacy of IFNβ therapy [4,6,8]. However, there is no consensus on the immunomodulatory role of anti-IFNβ antibodies, and some authors have published findings that refute their reported antitherapeutic effect [19][20][21]. The discrepancies among the published data may be explained by differences in both methodology and numbers of patients analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study in patients with multiple sclerosis showed a significant decrease in the number of circulating T cells that expressed HLA-DR antigens and CD25 after 2 months of treatment, followed by a return to pretreatment levels after 3-12 months (14). This might be caused by down-regulation of IFN␤ receptors or the development of neutralizing antibodies to IFN␤ during treatment (15). The return to pretreatment values was, however, not associated with reduced clinical efficacy.…”
Section: Discussionmentioning
confidence: 76%
“…These data and others indicate that NAB reduces the biologic activity and therapeutic efficacy of IFN-β. [8][9][10][11][12] We report further follow-up of these individuals, and include data from a larger cohort of individuals who were at risk to develop NAB. The data demonstrate that the incidence of NAB remains at approximately 5%, even with more individuals followed for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%